A randomized, multicenter trial assessing the effects of rapastinel compared to ketamine, alprazolam, and placebo on simulated driving performance. Issue 1 (7th November 2021) - Su, Shengfang; Kay, Gary; Hochadel, Thomas; Rojo, Jonathan; Christopher Stein, J.; Boinpally, Ramesh; Periclou, Antonia
Abstract: N‐methyl‐D‐aspartate ionotropic glutamatergic receptor (NMDAR) modulators, including rapastinel and ketamine, elicit rapid and sustained antidepressant responses in patients with treatment‐resistant major depressive disorder. This phase I, randomized, multicenter, placebo‐controlled, five‐period, crossover, single‐dose study evaluated simulated driving performance of healthy participants ( N  = 107) after single doses of rapastinel slow intravenous (i.v.) bolus 900 and 1800 mg, alprazolam oral 0.75 mg (positive control), ketamine i.v. infusion 0.5 mg/kg (clinical comparator), and placebo ~ 45 min before driving. The primary end point was SD of lateral position (SDLP) during the 60‐min 100‐km simulated driving scenario. Additional measures of driving performance, sleepiness, and cognition were also evaluated. To assess effects over time, mean SDLP was calculated for each 10‐min interval of driving. Sensitivity of the assays was confirmed with alprazolam (all placebo comparisons p  < 0.02). Rapastinel 900 and 1800 mg did not significantly affect simulated driving performance compared to placebo (both p  > 0.5). Both rapastinel doses resulted in significantly less impaired driving compared to alprazolam or ketamine (all p  < 0.002); ketamine significantly impaired driving compared to placebo ( p  = 0.0001). Results for the additional measures were similar to the primary end point. No new safety signals were observed for any study interventions. This first study of rapastinel effects on simulated driving found that rapastinel 900 and 1800 mg did not impair driving performance, but ketamine 0.5 mg/kg resulted in significantly impaired driving performance. Ketamine's effects on driving were maintained for at least 105 min, indicating that clinicians should be vigilant to prevent or postpone driving in patients after ketamine treatment.